A 5-Pathway Signature Predicts Prognosis Based on Immune-Derived lncRNAs in Patients with Breast Cancer. (12th December 2022) - Liu, Bo; Zhu, Nian; Huo, Huixia; Long, Junqi; Ji, Xinchan; Li, Jinmeng; Zhuang, Xujie; Wang, Huina; Li, Lujia; Chen, Yuhaoran; Yang, Wei; Zhao, Shuangtao
Abstract : Background . Currently, predictive models were not developed based on the signaling pathway signatures of immune-related lncRNAs in breast cancer (BRCA) patients. Methods . We selected unsupervised hierarchical clustering algorithm to classify patients with BRCA based on the significant immune-derived lncRNAs from the TCGA dataset. And different methods including ESTIMATE, ImmuneCellAI, and CIBERSORT were performed to evaluate the immune infiltration of tumor microenvironment. Using Lasso regression algorithm, we filtered the significant signaling pathways enriched by GSEA, GSVA, or PPI analysis to develop a prognostic model. And a nomogram integrated with clinical factors and significant pathways was constructed to predict the precise probability of overall survival (OS) of BRCA patients in the TCGA dataset ( n = 1, 098) and another two testing sets ( n = 415). Results . BRCA patients were stratified into the PC ( n = 571) and GC ( n = 527) subgroup with significantly different prognosis with 550 immune-related lncRNAs in the TCGA dataset. Integrated analysis revealed different immune response, oncogenic signaling, and metabolic reprograming pathways between these two subgroups. And a 5-pathway signature could predict the prognosis of BRCA patients between these two subgroups independently in the TCGA dataset, which was confirmed in another two cohorts from the GEO dataset. In the TCGA dataset, 5-year OS rate was 78% (95% CI: 73–84) vs. 82% (95% CI: 77–87) for the PC and GC group (HR = 1.63 (95% CI: 1.17–2.28), p = 0.004 ). The predictive power was similar in another two testing sets (HR > 1.20, p < 0.01 ). Finally, a nomogram is developed for clinical application, which integrated this signature and age to accurately predict the survival probability in BRCA patients. Conclusion . This 5-pathway signature correlated with immune-derived lncRNAs was able to precisely predict the prognosis for patients with BRCA and provided a rich source characterizing immune-related lncRNAs and further informed strategies to target BRCA vulnerabilities.